Perception of Environmental Problem in Elementary Students’ Mind Maps - Karatekin, Kadir (Elsevier BV, 2013)
AbstractThe purpose of this study is to define elementary students’ perception of environmental problems via mind mapping technique. For this purpose, 88 students of 5th, 6th, 7th, and 8th grades at an elementary school in Ankara were asked to draw their own mind maps related to environmental problems. Mind maps drawn were qualitatively analyzed through document review. Results showed that elementary students were most concerned about environmental issues such as air pollution, water pollution, problem of waste, and global warming. Due to environmental problems, students mostly had feelings of grief, fear, and displeasure. The study showed that students’ level of trust in solutions to environmental problems was low.
Keywords: mind map; environmental problems; Elementary; perception; concern about environment.; 13. Climate action; 4. Education; 6. Clean water